Early Pregnancy Diagnosis Using Milk Progesterone Kits in Etawah Cross Goat (Capra hircus) - Milona Elsa Nova; Ginta Riady; Juli Melia (Jurnal Medika Veterinaria, 2014)
This study aims to determine the effectiveness and accuracy of milk progesterone kit as an early pregnancy diagnosis tool for Etawah cross goat. This study used 9 lactating female goats with weight in the range of 35-51 kgs and the ages ranging from 2 to 2.5 years old. Eight goats were subject to estrous synchronisation protocol using progesterone implant (CIDR-G) followed by prostaglandin administration and one goat was left to show natural estrous. Early pregnancy diagnosis using milk progesterone kits was carried out on day 18 until 22 following services. The accuracy of the kits for early pregnancy diagnosis was subsequently confirmed using ultrasonography (USG) examination on day 35 following services. The results of this study showed that estrous response by synchronization was 50%. Whereas one female goat showed estrous sign naturally and was subject to pregnancy diagnosis procedure using the milk progesterone kits after natural mating. Pregnancy diagnosis using milk progesterone kits and subsequent confirmation using USG was carried out in five goats (4 synchronized females and mated and 1 naturally estrous female and mated naturally). All 5 female goats showed negative results following pregnancy diagnosis using the kits throughout the whole 5 days examinations. While diagnosis of pregnancy as confirmed by USG showed one goat (number 6) positive. It can be concluded that milk progesterone kits on dairy cows are less effective for diagnosing pregnancy on Etawah cross goat. The accuracy of the kits for pregnancy diagnosis of not-pregnant status is 80% after confirmation using USG.Key words: CIDR-G, Ettawah goats, milk progesterone kits, ultrasonography